Both Underweight and Obesity Are Associated With an Increased Risk of Coronavirus Disease 2019 (COVID-19) Severity - Ye, Pian; Pang, Ran; Li, Ling; Li, Hua-Rong; Liu, Shuang-Lin; Zhao, Lei (Frontiers in Nutrition, 2021)
Introduction: As coronavirus Disease 2019 (COVID-19) has evolved into a global pandemic, increasing numbers of reports have linked obesity to more severe COVID-19 illness and death. However, almost all the studies focused on an increased risk of mortality or intensive care unit (ICU) admission among hospitalized obese patients with COVID-19. Is obesity also associated with the incidence of acute lung injury (ALI) in the patients with COVID-19? How about underweight patients? The answer is lacking. Therefore, our following research will answer the above two questions. Methods: We collected and analyzed epidemiologic, demographic, clinical, and laboratory data from 193 confirmed cases of COVID-19 at Union Hospital, Tongji Medical College, Huazhong University of Science and Technology in Wuhan, China, between January 1, 2020, and March 13, 2020. They were followed up until April 15, 2020. Underweight was defined by body mass index (BMI) lower than 18.5 kg/m2, normal weight by 18.5−23.9 kg/m2, overweight by 24.0−27.9 kg/m2, and obesity as ≥28 kg/m2. Results: Among these patients, 5.70% were underweight, 58.03% were normal weight, 27.98% were overweight, and 8.29% were obese. Underweight patients were more likely to have a headache (P = 0.029). Obese patients were more likely than other groups to experience a decline in lymphocyte counts (P = 0.038), an increase in C-reactive protein (CRP; P = 0.023), bilateral multiple mottling, and ground glass opacity in the lungs (P = 0.007). Besides, the proportion of patients receiving human immunoglobulin + systematic corticosteroids treatment is the highest among the obese group compared with other BMI groups. After adjusting for potential confounders, underweight patients had a 6.483-fold higher (P = 0.012), and obese patients showed a 5.965-fold higher odds for developing ALI than normal-weight patients (P = 0.022). In addition, underweight patients were 3.255 times more likely than normal-weight patients to develop secondary infections (P = 0.041). Conclusions: Our study showed that both underweight and obese patients with COVID-19 tend to develop ALI compared with normal-weight patients. Underweight patients were more likely to develop a secondary infection than other patients.